The Effect of Science, Technology, Engineering, and Mathematics (STEM) Approaches on Critical Thinking Skills Using PBL Learning Models - I Putu Yogi Setia Permana; I Dewa Putu Nyeneng; I Wayan Distrik (Universitas Lambung Mangkurat, 2021)
The purpose of this study was to determine the effect of Science, Technology, Engineering, and Mathematics (STEM) approach to the improvement of critical thinking skills using Problem Based Learning (PBL) models. The population of the research was all of the 10th grade IPA students in SMA Negeri 7 Bandar Lampung which were 233 students. The selection of research sample used a purposive sampling technique with the sample of class X IPA 5 that consisted of 31 students as the experimental group and the class X IPA 6, which was 30 students, as the control group. The research design used Non-Equivalent Pretest Posttest Control Group Design. Data were tested by N-gain analysis, normality test, homogeneity test, Mann-Withney U Test Effect size test. The results showed that there was a significant effect of the STEM approach in improving critical thinking skills as indicated by the Sig. (2-Tailed), which was less than 0.05, 0.000, and the average value of N-gain (g) critical thinking skills in the experimental class was 0.73 (high category) while the control class was 0.56 (medium category). Effect size showed a value (d) of 1.49 included in high category. It can be concluded that the application of STEM approach using PBL learning model can improve students critical thinking skills. Implications of the study are discussed. The use of the STEM approach using PBL learning model can be used as an alternative for teachers as an effort to improve students' critical thinking skills.